EKSISTENSI KECENDERUNGAN MEMILIKI DALAM ISLAM - Amir Hamzah Amir (Institut Agama Islam Muhammadiyah Sinjai, 2021)
Humans as a bearing creature have a veriety of potential and tendency in it self that is a fitrah human. One of the laeries owned almost all human beings are a nature tendency like towards worldly like, treasure, thornes, couples, and families. This part of the nature of the human God who gives to them. According to the Koran, Alloh is the absolute owner of wealth. Wealth as private asset is intended for direct human character and attitude to look for, own, and use it on the right path. Wealth as belonging together meant that all humans have the opportunity to look for wealth, no one is given the right to strict circulation of wealth in the human environment and in every one’s wealth there are parts of others. The method used in this journal is descriptive that presents a description is and more profound analysis because the object of review is only in verses then the appropriate approach is the Tafsir Maudhu’i. Function of wealth as a provision for worship, support life, as aztest of faith, the support to be a leader, and one of the jewelry of life. Obtaining wealth should not be by way of vanity, its use must be balanced, the management must be careful, honest, sincere, and transparent and able to provide benefits to the community. Therefore it is necessary to have rules that regulate human needs so as not to violate and control the rights of others, especially related to property and ownership in islam.